Safety of using genetic engineering biological agents in rheumatoid arthritis - N V Chichasova; E L Nasonov; N V Chichasova; E L Nasonov (Современная ревматология)
The paper reviews the current trials of the safety of using genetic engineering biological agents (GEBA) in patients with rheumatoid arthritis. It is stated that before its start, GEBA therapy calls for thorough screening of patients to rule out communicable diseases (including tuberculosis) or a high risk for infections (chronic shin ulcers, severe diabetes mellitus, persistent lung infection, and the presence of a urinary catheter), cancer, and severe visceral diseases. The baseline liver status, a cardiovascular risk, neutropenia in response to basic anti-inflammatory drugs (BAID) should be also borne in mind. It is noted that when patients are correctly selected and possible adverse reactions are monitored, GEBA therapy is not worse tolerated than is BAID therapy.